ANALISIS FAKTOR PENYEBAB PERILAKU SELF HARM PADA SISWA - Najia Barouatul Aufa; Ali Daud Hasibuan (UIN Sumatera Utara Medan, 2024)
Self-harm is a form of behavior carried out by individuals to overcome emotional pain by injuring themselves, carried out intentionally and consciously but charged with suicidal intent. This research aims to determine the factors that cause self-harm behavior in students. This research uses a qualitative method with a case study type. The collection techniques used were interviews and documentation (voice recordings). The respondents in this study consisted of two 8th grade teenage girls from MTs schools. Muallimin UNIVA Medan who uses the pseudonyms Sari and Lina. One of them is that Lina has engaged in self-harm behavior. The research results show that the factors that cause self-harm are self-harm such as coping with stress, emotional dysregulation, loneliness, social support, parenting patterns and family problems. A comparison between the two respondents showed that respondent Lina showed significantly negative experiences with the factors causing self-harm compared to respondent Sari. Meanwhile, Sari respondents viewed the factors that cause self-harm more positively, this was based on the high level of attention and social support they received from their families.